Numerical Analysis of Reinforced Concrete Structures with Soil-Structure Interaction under Different Earthquake Accelerations - Yıldız, Serhat; Gör, Mesut (Dicle University, 2025)
Turkey, being a country with a high density of active fault lines, is prone to earthquakes with destructive effects, particularly in certain regions. Reducing these destructive effects is one of the main objectives of civil engineering. When designing structures, it is essential to consider not only the details of the structure but also the properties and behaviors of the soil. In this study, the effects of the number of basement floors on the soil-structure interaction of a seven-story reinforced concrete building under earthquake loading are investigated. The models and analyses were created using the SAP2000 and PLAXIS 2D software. Three different models of the seven-story building were generated, with the number of basement floors set to 1, 2, and 3, respectively. The models were analyzed under four different earthquake records, and the horizontal and vertical displacements of the structures were determined. A total of 24 analyses were conducted, considering two different software, three different models, and four different earthquake ground motion records. The results showed the impact of the increase in the number of basement floors on the horizontal and vertical displacements, and the results from the two software were evaluated.

Türkiye, aktif fay hatlarının yoğun olduğu bir ülke olması sebebi ile özellikle bazı bölgelerinde yıkıcı etkilere sahip depremler meydana gelebilmektedir. Bu yıkıcı etkiyi azaltmak ise inşaat mühendisliğinin temel amaçlarından biridir. Yapı tasarımı yapılırken, yapının detayları kadar zeminlerin de özellikleri ve davranışları göz önünde bulundurulması gerekmektedir. Bu çalışmada, farklı bodrum kat sayısına sahip 7 katlı betonarme yapıların, deprem etkisi altında analizleri yapılarak, bodrum kat sayısının zemin-yapı etkileşimi üzerindeki etkisi araştırılmıştır. Oluşturulan modeller ve analizler için SAP2000 ve PLAXIS 2D programları kullanılmıştır. 7 kata sahip yapının, bodrum sayısı 1, 2 ve 3 olacak şekilde değiştirilerek 3 farklı model oluşturulmuştur. Oluşturulan modellerin 4 farklı deprem etkisi altındaki analizleri yapılıp yapıların yatay ve düşey deplasmanları bulunmuştur. 2 farklı program 3 farklı model ve 4 farklı deprem ivme kaydı kullanılarak toplam 24 analiz yapılmıştır. Analizler sonucunda bodrum sayısındaki artışın yatay ve düşey deplasmanlar üzerindeki etkisi görülmüş, iki programın sonuçları değerlendirilmiştir.
Farklı Deprem İvmeleri Altında Betonarme Yapıların Zemin Yapı Etkileşimi ile Nümerik Analizi
Keywords: Civil Geotechnical Engineering; İnşaat Geoteknik Mühendisliği; Soil Mechanics in Civil Engineering; İnşaat Mühendisliğinde Zemin Mekaniği